LA AUTOEVALUACIÓN NO ES EL CAMINO DIRECTO PARA LA ACREDITACIÓN UNIVERSITARIA - Valencia Pomareda, Herbert (2007)
The university accreditation looks for, mainly, the academic quality or labor competencies that our users or enterprises need from the leaving students. As a consequence, it is not advisable to get the accreditation by means of self-evaluation. To get the required quality, it is necessary to know the educational needs of the society.